Reliability of Telepathology for Frozen Section Service - Uwe Wellnitz; Bernd Binder; Peter Fritz; Godehard Friedel; Peter Schwarzmann (Analytical Cellular Pathology)
One of the most promising applications of telepathology (pathology at a distance by electronic transmission of images in pathology) is frozen section diagnosis, especially because by means of this tool operations requiring an intraoperative histopathological diagnosis are feasible at hospitals without a pathologist on‐site. For the introduction of this diagnostic tool into pathologist's daily practice the evidence of its diagnostic accuracy comparable to that of the conventional frozen section diagnosis is crucial.